2004
DOI: 10.1002/mrc.1425
|View full text |Cite
|
Sign up to set email alerts
|

Complete assignment of 19F, 1H and 13C NMR spectra of monomers and precursors towards bridge trifluoromethylated poly(p‐phenylenevinylene)

Abstract: The complete assignment of 19F, 1H and 13C NMR spectra of 11 trifluoromethylated and four bistrifluoromethylated monomers for bridge trifluoromethylated poly(p-phenylenevinylene) is described. The combination of one-dimensional 19F, 1H and 13C spectra, long-range fluorine couplings and the two-dimensional techniques of direct and long-range HETCOR (J = 140 and 8 Hz) permitted full resonance assignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is also found that the average difference of coupling constants obtained by these two methods is 0.512. For a series of methyl aldopyranosides (12)(13)(14)(15)(16)(17)(18)(19)(20) as given in Scheme 5, Table 5 shows good agreement between experimental 3 J CH values and those predicted through Equation (3) using the torsional angles obtained by X-ray spectroscopy. [112]…”
Section: Effect Of Substituents On J-couplingmentioning
confidence: 62%
See 1 more Smart Citation
“…It is also found that the average difference of coupling constants obtained by these two methods is 0.512. For a series of methyl aldopyranosides (12)(13)(14)(15)(16)(17)(18)(19)(20) as given in Scheme 5, Table 5 shows good agreement between experimental 3 J CH values and those predicted through Equation (3) using the torsional angles obtained by X-ray spectroscopy. [112]…”
Section: Effect Of Substituents On J-couplingmentioning
confidence: 62%
“…[5] The employment of long-range proton-fluorine and carbon-proton couplings helped in the complete assignment of 1 H, 13 C and 19 F NMR spectra of trifluoromethylated poly(pphenylenevinylene) and cyclopentane derivatives. [17,18] The use of long-range proton-fluorine couplings in describing the glycosidic torsion angle dependence of fluorinated RNA molecules has been demonstrated. [19] It also provides the signature of the hydrogen bond in either small or medium-sized molecules such as benzamide [20] and its related compounds or the side-chain residue of protein molecules, thereby giving access to dynamic information about the protein side chains.…”
Section: Introductionmentioning
confidence: 99%